Women Who Dared : 52 Stories of Fearless Daredevils, Adventurers & Rebels - Skeers, Linda; Gosling, Livi (Naperville, Illinois : Sourcebooks, Inc., 2017)
Women have been doing amazing, daring, and dangerous things for years, but theyre rarely mentioned in our history books as adventurers, daredevils, or rebels. This new compilation of brief biographies features women throughout history who have risked their lives for adventure - many of who you may not know, but all of whom youll WANT to know, such as: Minnie Spotted Wolf, the first Native American marine; Valentina Tereshkova, the first woman to fly in space; Beatrice Ayettey, the first female ship captain from Ghana; and many more! This is the perfect read for anyone who wants to know what it means to explore, discover, play, climb, and fight like a girl!
Keywords: Women daredevils -- Biography; Juvenile literature; Women adventurers -- Biography; Juvenile literature; Adventure and adventurers -- Biography; Juvenile literature; Women heroes -- Biography; Juvenile literature; Dissenters -- Biography; Juvenile literature; Women -- Biography; Juvenile literature; Action and adventure fiction; Biographies; Juvenile works; Action and adventure fiction